Antioxidant and Elastase Inhibitor from Black Soybean (Glycine max L.) and Its Compound (Daidzein) - Cendy Juliana; I Nyoman Ehrich Lister; Ermi Girsang; Ali Napiah Nasution; Wahyu Widowati (Journal of Biomedicine and Translational Research, 2020)
Background: Skin aging occurs along with age. Genetic, nutrients, hormones, and sun exposure can affect directly and indirectly the structure of the skin. These things will induce an increase in free radicals which disrupts one of the most important enzymes in the extracellular matrix which is elastase enzyme. High enzyme synthesis will cause skin wrinkle. Free radicals can be inhibited by the presence of antioxidants. The plant contains natural phytochemical compounds which act as antioxidants and anti aging. Black soybeans are rich in daidzein compound, which protect against free radicals and prevent premature aging.Objective: This research evaluates the antioxidant and antiaging potential of Black Soybean (Glycine max L.) extract and its compound, daidzein.Methods: Analysis of antioxidants from black soybean extract and daidzein were carried out using ABTS scavenging activity assay. The antiaging assay was carried out through inhibition of elastase enzyme.Results: Black soybean extract had lower IC50 value of ABTS scavenging activity around 77.39±4.05 μg/ml better than daidzein with IC50 of 83.34±3.89 μg/ml. The results of elastase inhibition activity assay showed that daidzein compound has a lower IC50 value, 57.35±5.64 μg/ml compared to black soybean extract with IC50 value, 93.36±6.39 μg/ml.Conclusion: Black soybean extract had higher antioxidant. Daidzein had better elastase inhibition activity compared to black soybean extract.